TRANSFORMASI PEMBELAJARAN BERBASIS PROYEK: OPTIMALISASI EVALUASI DAN REFLEKSI DALAM MENINGKATKAN KOMPETENSI ABAD 21 - Syaefulloh Syaefulloh; Nina Rosyidah; Ida Amelia (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Project-Based Learning (PjBL) has been recognized as an effective method for developing 21st-century competencies; however, its success is often hindered by a lack of focus on process evaluation and critical reflection. This study aims to analyze the urgency of transforming evaluation paradigms and the role of guided reflection in enhancing instructional quality within the PjBL model. Using a qualitative approach with a descriptive-analytical method, data were collected through observation, in-depth interviews, and documentation studies of the learning process. The research results indicate three main findings: first, an authentic evaluation design that includes process, peer, and self-assessment is capable of capturing student competencies more comprehensively than traditional exams. Second, the implementation of guided reflection through learning journals and metacognitive discussions is proven to strengthen students' self-awareness regarding learning strategies and problem-solving. Third, the synergy between accurate evaluation results and honest reflection creates an adaptive and meaningful learning ecosystem that fosters a growth mindset in students. This study recommends that educators systematically integrate reflection sessions as an inseparable part of the evaluation cycle in every learning project.